If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a = 4a + 7 Reorder the terms: 5a = 7 + 4a Solving 5a = 7 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 5a + -4a = 7 + 4a + -4a Combine like terms: 5a + -4a = 1a 1a = 7 + 4a + -4a Combine like terms: 4a + -4a = 0 1a = 7 + 0 1a = 7 Divide each side by '1'. a = 7 Simplifying a = 7
| -6(4X+7)=-66 | | X+16=54 | | 2x(3xy-3x+2y)= | | 5(x-3)=2(x-15) | | 2x+4=x-10 | | -16+2x=-24+13x | | X+9-4=17 | | 6x+2(1+2x)=4(-2+5) | | -0.4(-0.6)= | | 3w(w+2)=0 | | (x+2)(x+1)=10 | | -2(7m-8)-3=-5(1+4m)+8m | | 3x(2xy+3y-2x)= | | X-12=43 | | 5-5(6-5)= | | 6(1-4p)=-8(-4+4p)-2 | | 61-3x=13-9x | | -6x-3.2=-3x+4.4 | | -9(6+n)=-54 | | -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x |